FAKTOR KEPATUHAN MASYARAKAT KOTA DENPASAR PADA PROTOKOL KESEHATAN COVID-19 - MERIANI, IA KOMANG; SUKARSA, I KOMANG GDE; KENCANA, EKA N; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 11 No 4 (2022), 2022)
Coronavirus disease (COVID-19) pandemic makes peoples around the world face many difficulties to do their daily activities in a normal way. To reduce the impacts of this deathly virus as well to suppress its spread, countries in the world, including Indonesia, have made protocols that regulate the activities of their citizens. This study aims to determine the group of factors that influence the compliance of Denpasar residents with the Covid-19 prevention health protocol. Population of this study is Denpasar residents aged 15 to 64 years. Applying proportional random sampling technique, 250 people who lived in four sub-districts in Denpasar were selected as respondents of the study. Questionnaire that has proven the validity of its items are distributed from March to April 2022. To determine group of factors associated with adherence to the implementation of COVID -19 protocol, explanatory factor analysis is utilized to group 24 initial items on questionnaire. The results demonstrate 7 of the 24 items did not have adequate criteria to be included as forming factors. The rests prove 6 factors behind the compliance of COVID-19 protocol, i.e. information seeking, people trust toward the protocol, infected history, caring for self and family health, comfortable and feels safe wearing a mask, and sanctions for protocol violations. These factors extracted the variance of original data around 77 percent.